The first draft genome assembly and data analysis of the Malaysian mahseer (Tor tambroides) - Melinda Mei Lin, Lau; Leonard Whye Kit, Lim; Chung, Hung Hui; Gan, Han Ming (Elsevier B.V., 2023)
The Malaysian mahseer (Tor tambroides), one of the most valuable freshwater fish in the world, is mainly targeted for human consumption. The mitogenomic data of this species is available to date, but the genomic information is still lacking. For the first time, we sequenced the whole genome of an adult fish on both Illumina and Nanopore platforms. The hybrid genome assembly had resulted in a sum of 1.23 Gb genomic sequence from the 44,726 contigs found with 44 kb N50 length and BUSCO genome completeness of 87.6%. Four types of SSRs had been detected and identified within the genome with a greater AT abundance than that of GC. Predicted protein sequences had been functionally annotated to public databases, namely GO, KEGG and COG. A maximum likelihood phylogenomic tree containing 52 Actinopterygii species and one Sarcopterygii species as outgroup was constructed, providing first insights into the genome-based evolutionary relationship of T. tambroides with other ray-finned fish. These data are crucial in facilitating the study of population genomics, species identification, morphological variations, and evolutionary biology, which are helpful in the conservation of this species.